ANALISIS FRAMING PEMBERITAAN LARANGAN THRIFTHING PADA MEDIA BATAMPOS.CO.ID DAN BATAMNEWS.CO.ID - Builalaq, Viviana; Abidin, Sholihul (SCIENTIA JOURNAL, 2024)
After the policy of prohibiting the import of used clothing written in Permendag No. 40 of 2022 concerning Export-Prohibited Goods and Import-Prohibited Goods which received many rejection from the public, especially the import used clothing business in Batam City. Departing from this, researchers want to raise the news regarding the ban on thrifting in Batam City on the online media batampos.co.id and batamnews.co.id . This study aims to find out the perspectives of the media batamnews.co.id and batampos.co.id in presenting this ban on thrifting. The study used documentation and observation techniques. The analysis method used by researchers is Zhongdang Pan Gerald M. Kosici's frame analysis model. Data collection through written or loaded archives sourced from the online media batampos.co.id and batamnews.co.id March-April 2023, which contains news about thrifting ban in Batam City. The results of this study, the online media batampos.co.id , which framed the news of the thrifting ban in Batam City, discussed in detail the government's actions and assertions regarding the prohibition of used imported goods from illegal entry, while batamnews.co .id tends to describe in detail the conditions of traders and people who disagree regarding the import ban on secondhand goods in Batam City